Use of Patient-Reported Experience Measures in Pediatric Care: A Systematic Review - Bele, Sumedh; Teela, Lorynn; Zhang, Muning; Rabi, Sarah; Ahmed, Sadia; van Oers, Hedy Aline; Gibbons, Elizabeth; Dunnewold, Nicole; Haverman, Lotte; Santana, Maria J. (Frontiers in Pediatrics, 2021)
Introduction: Patient-reported Experience Measures (PREMs) are validated questionnaires, that gather patients’ and families’ views of their experience receiving care and are commonly used to measure the quality of care, with the goal to make care more patient and family-centered. PREMs are increasingly being adopted in pediatric population, however knowledge gaps exist around understanding the use of PREMs in pediatrics. Objective: To identify and synthesize evidence on the use of PREMs in pediatric healthcare settings and their characteristics. Evidence review: Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines governed the conduct and reporting of this review. An exhaustive search strategy was applied to MEDLINE, EMBASE, PsycINFO, Cochrane Library, and CINAHL databases to identify relevant peer-reviewed articles from high-income countries. Additionally, grey literature was searched to capture real-world implementation of PREMs. All the articles were screened independently by two reviewers in two steps. Data was extracted independently, synthesized, and tabulated. Findings from grey literature was synthesized and reported separately. Risk of bias for the studies identified through scientific databases was assessed independently by two reviewers using the National Institutes of Health Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: The initial search identified 15,457 articles. After removing duplicates, the title and abstracts of 11,543 articles were screened. 710 articles were eligible for full-text review. Finally, 83 articles met the criteria and were included in the analyses. Of the 83 includes studies conducted in 14 countries, 48 were conducted in USA, 25 in European countries and 10 in other countries. These 83 studies reported on the use of 39 different PREMs in pediatric healthcare settings. The grey literature retrieved 10 additional PREMs. The number of items in these PREMs ranged from 7 to 89. 23 PREMs were designed to be completed by proxy, 10 by either pediatric patients or family caregivers, and 6 by pediatric patients themselves. Conclusion And Relevance: This comprehensive review is the first to systematically search evidence around the use of PREMs in pediatrics. The findings of this review can guide health administrators and researchers to use appropriate PREMs to implement patient and family-centered care in pediatrics.